Labour, capital and the state in the St. Helena Bay fisheries c.1856 - c.1956 - Van Sittert, Lance (Department of Historical Studies, 2016)
This thesis deals with the history of the St Helena Bay inshore fisheries, 1856-1956. Fishing has long been neglected by social and economic historians and the myths propagated by company and popular writers still hold sway. The thesis challenges these by situating commercial fishing at St Helena Bay in the context of changing regional, national and international economies and showing how it was shaped and conditioned by the struggle for ownership of the marine resource between labour and capital, mediated by the state. The thesis is organised chronologically into three epochs. In each the focus moves from macro to micro, tracing the processes of class formation, capital accumulation and state intervention. The first epoch (c.1856-c.1914) examines the merchant fisheries, the second (c.1914-c.1939) the crayfish canning industry and the third ( c.1939-c.195) secondary industrialisation. It is argued that the common property nature of the marine resource and non-identity between labour and production time in fishing created obstacles to capitalist production, discouraging investment and allowing petty-commodity production to flourish. The latter mediated the vagaries of production through a share system of co-adventuring which enabled owners to avoid paying a fixed wage. This system's impact on the nature and consciousness of fishing labour is examined as is its vulnerability to capture by other capitals through insecure land tenure and credit. Fishing capital, in both its merchant and productive guises was dependent on articulation with petty-commodity production to provide it with commodities or raw material and bear the cost of reproducing labour. Articulation was hampered at St Helena Bay both by the persistence of merchant capital and the rent and labour interests of Sandveld agriculture. The origins and effect of this situation on the fisheries is detailed and discussed, highlighting the importance of agricultural capital's political influence with the colonial and provincial state in blocking or subverting the development of productive capital. The advent of the interventionist central state in the 1930s undermined merchant and farmer dominance of the fisheries and cleared the way for the articulation of petty-commodity primary production with secondary industry during and after the Second World War. This articulation was facilitated by the central state restricting access to the marine · resource and investing heavily in marine research and infrastructure to roll-back the natural constraints on fishing and create the conditions for the establishment of a stable capitalist production regime.